SIKAP KONSUMEN TERHADAP TABUNGAN PESIRAH PADA BANK SUMSEL-BABEL KANTOR CABANG PEMBANTU BAYUNG LENCIR - Fera Anggraini (Jurnal Dinamika Manajemen, 2015)
This research was written by Fera Anggraini under the guidance of Suswita Roza, SE, MM. This thesis is entitled "Analysis of Consumer Attitudes towards Pesirah Savings at Bank Sumsel-Babel Kcp Bayung Lincir". The purpose of this study is to determine consumer attitudes towards the Pesirah savings of Bank Sumsel-Babel KCP Bayung Lincir and to analyze consumer attitudes towards Pesirah savings of Bank Sumsel-Babel KCP Bayung Lincir. This study took a sample of 100 respondents using a cluster sampling sample, namely where the sample was taken randomly as much as needed. The method used in this study is to use the fishbein model to measure how much consumer attitudes are towards the Pesirah savings of Bank Sumsel-Babel KCP Bayung Lincir. To measure the level of evaluation and consumer confidence, the Likert scale technique is used. The results showed that the consumer's attitude towards the Pesirah savings of Bank Sumsel-Babel KCP Bayung Lincir was that consumers (customers) were quite good about the services provided by the Bank Sumsel-Babel KCP Bayung Lincir.